Inhaled Corticosteroids and COVID-19 Risk and Mortality: A Nationwide Cohort Study - Choi, Jae Chol (J Clin Med, 2020)
Inhaled corticosteroids (ICS) could increase both the risk of coronavirus disease 2019 (COVID-19) and experiencing poor outcomes. To compare the clinical outcomes between ICS users and nonusers, COVID-19-related claims in the Korean Health Insurance Review and Assessment database were evaluated. To evaluate susceptibility to COVID-19 among patients with COPD or asthma, a nested case-control study was performed using the same database. In total, 7341 patients were confirmed to have COVID-19, including 114 ICS users and 7227 nonusers. Among 5910 patients who were hospitalized, death was observed for 9% of ICS users and 4% of nonusers. However, this association was not significant when adjusted for age, sex, region, comorbidities, and hospital type (aOR, 0.94; 95% CI, 0.43–2.07). The case-control analysis of COPD compared 640 cases with COVID-19 to 2560 matched controls without COVID-19, and the analysis of asthma compared 90 cases with COVID-19 to 360 matched controls without COVID-19. Use of ICS was not significantly associated with COVID-19 among patients with COPD (aOR, 1.02; 95% CI, 0.46–2.25) or asthma (aOR, 0.38; 95% CI, 0.13–1.17). Prior ICS use was not significantly associated with COVID-19 in patients with COPD or asthma, nor with clinical outcomes among patients with COVID-19.